Creativity Development of Students of SMA 20 Makassar Through Goes to School Programa 2 RRI Makassar Activities - Suarni Syam Saguni; Tri Ananda; Hernika Hernika; Hasmawani Rasyid (IPTEK: Jurnal Hasil Pengabdian kepada Masyarakat, 2022)
Abstract. Creativity is a person's ability to generate new ideas that are effective and ethical. The Goes To School activity which is carried out face-to-face (down directly at SMA 20 Makassar) is based on the aim of honing and developing students' ideas, ideas, and creativity as well as providing space for students to express their creativity according to their creativity in this digital era. This activity consists of two competitions, namely the video challenge (how to streaming) and broadcast (students become broadcasters). The participants of this competition are students of SMA 20 Makassar and through this competition it is hoped that students can improve their creativity, public speaking, and other ideas.Keywords: Creativity, Goes To School, RRI Makassar